Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Kementerian Pekerjaan Umum Balai Prasarana Permukiman Wilayah Maluku - Jihan Saskia Mardani; Aris Hidayat (CV. ITTC INDONESIA, 2025)
The importance of human resources for every organization is expected to improve employee performance, for that human resources need to have reliable competencies or skills in every job, because the existence of reliable competencies can directly improve employee performance. The research method used is a quantitative method by conducting direct research to employees at the Ministry of Public Works of the Maluku Regional Settlement Infrastructure Center. The number of samples was 49 respondents and was processed using SPSS software version 21. In the results of the partial determination coefficient test, the value of the determination coefficient of variable X1 was 0.196 and the strength of the relationship between variables X1 and Y was 19.6%. The X2 variable is 0.031, the relationship strength between the X2 and Y variables is 31%. In the results of the simultaneous determination coefficient test, an R square value of 0.343 was obtained, the relationship between the variables X1 and X2 was 34.3%. It shows that the variables of Competency and Work Environment have a simultaneous positive effect on the variables of Employee Performance.